2018
DOI: 10.3389/fnmol.2018.00089
|View full text |Cite
|
Sign up to set email alerts
|

SAHA (Vorinostat) Corrects Inhibitory Synaptic Deficits Caused by Missense Epilepsy Mutations to the GABAA Receptor γ2 Subunit

Abstract: The GABAA receptor (GABAAR) α1 subunit A295D epilepsy mutation reduces the surface expression of α1A295Dβ2γ2 GABAARs via ER-associated protein degradation. Suberanilohydroxamic acid (SAHA, also known as Vorinostat) was recently shown to correct the misfolding of α1A295D subunits and thereby enhance the functional surface expression of α1A295Dβ2γ2 GABAARs. Here we investigated whether SAHA can also restore the surface expression of γ2 GABAAR subunits that incorporate epilepsy mutations (N40S, R43Q, P44S, R138G)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…This is corroborated by previous work in oocytes which showed reduced whole-cell currents for these mutants (Niturad et al, 2017). Decreased cell surface expression reduces overall inhibition, resulting in the manifestation of epilepsy phenotypes (Fisher, 2004;Durisic et al, 2018;Shi et al, 2019). However, it may also result in the preferential expression of receptors lacking the α3 subunit which could in turn alter IPSC kinetics.…”
Section: Analysis Of Cell-surface Expression Efficiencysupporting
confidence: 86%
See 2 more Smart Citations
“…This is corroborated by previous work in oocytes which showed reduced whole-cell currents for these mutants (Niturad et al, 2017). Decreased cell surface expression reduces overall inhibition, resulting in the manifestation of epilepsy phenotypes (Fisher, 2004;Durisic et al, 2018;Shi et al, 2019). However, it may also result in the preferential expression of receptors lacking the α3 subunit which could in turn alter IPSC kinetics.…”
Section: Analysis Of Cell-surface Expression Efficiencysupporting
confidence: 86%
“…This apparent gain-of-function does not explain the associated pathology. However, further studies have shown that γ2 R43Q is retained in the endoplasmic reticulum (Durisic et al, 2018), resulting in reduced surface expression and synaptic targeting of the assembled receptor complexes (Frugier et al, 2007), which may explain the resulting loss of inhibitory control underlying the epileptic phenotypes.…”
Section: Effects Of Pathogenic Mutations On Ipscs Mediated By α3-contmentioning
confidence: 99%
See 1 more Smart Citation
“…As a broad HDACs inhibitor, SAHA has been shown to protect against seizure-induced brain damage through histone acetylation regulation (44). Intriguingly, SAHA was reported to enhance epilepsyassociated mutant GABA A receptor proteostasis in vitro (12)(13)(14). It has been demonstrated that SAHA increased the BiP protein level and the interaction between the mutant α1 subunit and calnexin, and thus partially corrected the transcription, folding and trafficking of mutant GABA A receptors (12).…”
Section: Hdacs Inhibition As a Potential Therapeutic Paradigm For Genetic Epilepsies Associated With Missense Gaba A Receptor Mutationsmentioning
confidence: 99%
“…Suberanilohydroxamic acid (SAHA, also known as Vorinostat) is an orally available histone deacetylases (HDACs) inhibitor that was approved by the US Food and Drug Administration for management of cutaneous T cell lymphoma (11). In vitro SAHA treatment has previously been shown to effectively enhance proteostasis, and thereby, partially correct the impaired function of GABA A receptors produced by epilepsy mutations associated with endoplasmic reticulum (ER) -associated protein degradation (12)(13)(14). Since SAHA crosses the blood brain barrier, we investigated its anticonvulsant efficacy and that of several established anticonvulsant drugs (valproic acid, levetiracetam, clonazepam, and carbamazepine) in vivo using the Tg(hGABRG2 F343L ) and Tg(hGABRG2 wt ) zebrafish models.…”
Section: Introductionmentioning
confidence: 99%